Penerapan Model Project Based Learning (PjBL) Pada Materi Asam Basa di Kelas XI IPA SMA Negeri 2 Tondano - Boy Kristi Siburian; Meytij Jeanne Rampe; John Zeth Lombok (Chemistry Department, Universitas Negeri Manado, 2021)
This research aims to determine the effect of implementing the PjBL model in improving the learning outcomes of students in the SMA Negeri 2 Tondano XI IPA class. This research is conducted in two cycles. The research phase includes planning, action, observation and reflection. The subjects of the study are students from the XI IPA SMA Negeri 2 Tondano class in the 2020/2021 academic year, a total of 18 students. Data collection techniques include observation, recording and testing instruments. Data analysis techniques include test results and observation data. The results show that the degree of completion of learning by 75 points has increased by 22.23%, among which the degree of completion of the learning achievements of Cycle I and Cycle II students is 66.67% and 88.90%, respectively. Based on the research results, the application of the PJBL model improves the learning outcomes of students.